Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/mnras/stz2020
|View full text |Cite
|
Sign up to set email alerts
|

The mass distribution of Galactic double neutron stars: constraints on the gravitational-wave sources like GW170817

Abstract: The merger event of double neutron star (DNS) system (GW170817) was detected by the gravitational-wave (GW) detectors (Advanced LIGO and Advanced Virgo) in 2017 for the first time, so their mass distribution has become a significant topic with the new round GW hunting (O3) in 2019. A few models (e.g. Gaussian, two-Gaussian, or mixture-Gaussian) were adopted to draw the mass distribution of observed Galactic DNS systems, however, there is no a confirmed model now due to the small size of DNS samples (N < 20)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…The default parameters are the mean m = 1.4 M , the mass dispersion σ m = 0.5 M , upper cut m cut,low = 1.1 M , m cut,high = 2.5 M ; we apply also a Gaussian spin model, with a smaller dispersion σ χ = 0.05. These choices are roughly agree with observations (Valentim et al 2011;Özel et al 2012;Kiziltan et al 2013;Miller & Miller 2015;Farrow et al 2019;Zhang et al 2019)…”
Section: Double Neutron Star Mergerssupporting
confidence: 90%
“…The default parameters are the mean m = 1.4 M , the mass dispersion σ m = 0.5 M , upper cut m cut,low = 1.1 M , m cut,high = 2.5 M ; we apply also a Gaussian spin model, with a smaller dispersion σ χ = 0.05. These choices are roughly agree with observations (Valentim et al 2011;Özel et al 2012;Kiziltan et al 2013;Miller & Miller 2015;Farrow et al 2019;Zhang et al 2019)…”
Section: Double Neutron Star Mergerssupporting
confidence: 90%
“…The event was classified as a neutron star-black hole (NSBH) merger, where the lighter component has a mass < 3 M , and the heavier component has a mass > 5 M , (LIGO Scientific Collaboration and Virgo Collaboration et al 2019b). The accuracy of this classification is dependent on the physical upper-limit for neutron star mass which is not well constrained, but may be less than the above definition (Zhang et al 2019;Cromartie et al 2019). The probability of there being matter outside the remnant object is < 1% (LIGO Scientific Collaboration and Virgo Collaboration et al 2019a), therefore the expected nature of any electromagnetic radiation from the merger (if any) is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The BH mass distribution observed so far in coalescing binaries is broad (The LIGO Scientific Collaboration et al 2018), extending up to 50 +16.6 −10.2 M , with the lightest BH carrying a mass 7.6 +1.3 −2.1 M , close to the mean BH mass in observed Galactic X-ray binaries of ∼ 7.8 ± 1.2 M ( Özel et al 2010). Double NS systems observed so far carry masses in the interval 1.165 M − 1.590 M (Zhang et al 2019), and the NS with the highest and best estimated mass is the radio pulsar J0740+6620 with M NS = 2.14 +0.10 −0.09 M in a lowmass binary (Cromartie et al 2019). Thus, observations appear to indicate a discontinuity between the observed mass distributions of NSs and stellar BHs, called mass gap", located approximately between ≈ 3 M (the maximum NS mass inferred from causality arguments) and ∼ 5 M (Lattimer & Prakash 2001).…”
Section: Introductionmentioning
confidence: 96%
“…The unbound NS material ("ejecta") is thought to produce kilonova emission (Lattimer & Schramm 1974;Li & Paczyński 1998;Metzger 2017). Moreover, Shapiro (2017); Paschalidis (2017); Ruiz et al (2018) showed that after a BHNS merger a relativistic jet can be launched, powering a short gamma-ray burst (sGRB) (Eichler et al 1989;Narayan et al 1992) and GRB afterglow emission (Sari et al 1998;D'Avanzo et al 2018;Ghirlanda et al 2018;Salafia et al 2019 (Zhang et al 2019), and the NS with the highest and best estimated mass is the radio pulsar J0740+6620 with M NS = 2.14 +0.10 −0.09 M in a lowmass binary (Cromartie et al 2019). Thus, observations appear to indicate a discontinuity between the observed mass distributions of NSs and stellar BHs, called mass gap", located approximately between ≈ 3 M (the maximum NS mass inferred from causality arguments) and ∼ 5 M (Lattimer & Prakash 2001).…”
Section: Introductionmentioning
confidence: 99%